Desain dan Implementasi Aplikasi Absensi Kepegawaian Berbasis Web Menggunakan Framework Laravel di Diskominfo Provinsi Jawa Barat - Firda Rosiana Tanjung; Venica Liptia (Jurnal Media Infotama, 2023)
Abstract—In all parts of the work division at Diskominfo, West Java Province, many information systems have been involved to support a series of work activities and information asset processing. As in one part of the division, namely the Employee and Public Relations Subdivision, where all staffing activities are not far from processing employee data. But the existing Employee Information System, especially in the employee attendance data processing feature, is still not well organized and not equipped with features that are more supportive for recording the attendance data. Some features that are not perfect, for example, are the daily attendance data feature, employee leaves data, and daily late and weekly late. In addition, further processing of data also still uses the help of Microsoft Excel or manually entering data and recapitulating data, so the processing takes a long time and is not efficient in the process. Given these problems, the authors designed a system design and implemented it into a new Employee Attendance Application. The purpose of designing this application is to create an information system that further optimizes the process of processing employee attendance data at West Java Diskominfo using system development technologies such as the Laravel Framework, PostgreSQL for database management, and using the Rest API for data integration.